2011
DOI: 10.1350/jcla.2011.75.3.707
|View full text |Cite
|
Sign up to set email alerts
|

Rebalancing, Reviewing or Rebranding the Treatment of Terrorist Suspects: The Counter-Terrorism Review 2011

Abstract: On 26 January 2011, the Home Secretary unveiled the outcome of the much-anticipated Counter-Terrorism Review, which straddled a political fault line between Conservative and Liberal Democrat policies. This article considers the impact of that review on the treatment of terrorist suspects. It is suggested that the review was both over-inclusive and under-inclusive in scope. While welcome reform and rebalancing has been instigated in some areas, the review represents missed opportunities in others, and on occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The significance of these changes is a matter of dispute. While the Independent Reviewer of Terrorism Legislation has insisted that the TPIMs system is "a new rather than a rebadged model" (Anderson 2012: 10), others have suggested that the changes constitute mere "rebranding" (Middleton 2011).…”
Section: Who Should Impose Tpims? Issues Of Normative Dualitymentioning
confidence: 99%
“…The significance of these changes is a matter of dispute. While the Independent Reviewer of Terrorism Legislation has insisted that the TPIMs system is "a new rather than a rebadged model" (Anderson 2012: 10), others have suggested that the changes constitute mere "rebranding" (Middleton 2011).…”
Section: Who Should Impose Tpims? Issues Of Normative Dualitymentioning
confidence: 99%
“…Control orders were limited and could only be imposed for a period of up to 12 months at a time. Their legality could also be challenged (Middleton, 2011). They created measures to supervise suspects through electronic tagging or by requiring them to remain in their homes (Fitzpatrick, 2003).…”
Section: The Uk Legislationmentioning
confidence: 99%